2020
DOI: 10.22271/chemi.2020.v8.i3ab.9496
|View full text |Cite
|
Sign up to set email alerts
|

Role of micronutrients in vegetable production: A review

Abstract: The nutrient elements which are required comparatively in small quantities are called as micro or minor nutrients or trace elements. Micronutrients are essentially as important as macronutrients to have better growth, yield and quality in plants. Proper plant nutrition is essential for successful production of vegetable crops. Integrated supply of micronutrients with macronutrients in adequate amount and suitable proportions is one of the most important factors that control the plant growth in vegetable crops.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…Hildebrandt et al (2015) suggested other useful functions of amino acids in plant cells, such as protein biosynthesis, signaling processes, energy producers, auxin biosynthesis and enzyme regulation influencing physiological processes, plant growth and development. micronutrients have tonic effects on the photosynthetic rate producing higher carbohydrate accumulation and its translocation from leaves (source) to fruits (sink) increasing the total yield (Marschner, 1995;Uchida, 2000;Jadhav et al, 2014;Sidhu et al, 2019).…”
Section: Effect Of Foliar Spray Treatmentsmentioning
confidence: 99%
“…Hildebrandt et al (2015) suggested other useful functions of amino acids in plant cells, such as protein biosynthesis, signaling processes, energy producers, auxin biosynthesis and enzyme regulation influencing physiological processes, plant growth and development. micronutrients have tonic effects on the photosynthetic rate producing higher carbohydrate accumulation and its translocation from leaves (source) to fruits (sink) increasing the total yield (Marschner, 1995;Uchida, 2000;Jadhav et al, 2014;Sidhu et al, 2019).…”
Section: Effect Of Foliar Spray Treatmentsmentioning
confidence: 99%
“…The combined treatments of amino acids and micronutrients solution recorded higher increases in the vegetative growth parameters of tomato plants may be linked to increases in the endogenous concentrations of Fe, Mn, and Zn photosynthetic pigments and total soluble proteins with the combination treatments. (Sakya & Sulandjari, 2019;Sidhu et al, 2019;Salim et al, 2019).…”
Section: Effect Of Foliar Spray Treatmentsmentioning
confidence: 99%
“…Foliar applications with amino acids have favorable essential roles in influencing nutrient uptake, chlorophyll synthesis, photosynthesis, metabolism, and enzyme activation in eggplant Salim et al 2019 andSidhu et al, 2019. The Ca is directly involved in improving photosynthesis, resulting in a high leaf number on tomato plants (Hussain et al, 2001). The Ca improved the leaf area by activating enzymes, photosynthesis, and carbohydrates metabolism (Bergmann, 1992;Hussain et al, 2001).…”
Section: Effect Of Foliar Spray Treatmentsmentioning
confidence: 99%